Future Generations and Contemporary Ethics. (1st November 2003) - Johnson, Lawrence E.
Future generations do not exist, and are not determinate in their make-up. The moral significance of future generations cannot be accounted for on the basis of a purely individualistic ethic. Yet future generations are morally significant. The Person-Affecting Principle, that (roughly) only acts which are likely to affect particular individuals are morally significant, must be augmented in such a way as to take into account the moral significance of Homo sapiens, a holistic entity which certainly does exist. Recent contributions to Environmental Values by Alan Carter and Ernest Partridge are criticised (but not entirely rejected).